1997
DOI: 10.1021/ie960194k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of High-Temperature Removal of H2S by Novel Metal Oxide Sorbents

Abstract: The behavior of different mixed oxides, including zinc titanates (ZT) and zinc ferrites modified with CuO (ZFC) or TiO2 (ZFT), as hot gas desulfurizing sorbents was investigated. The sorbents were prepared by calcination at 650 °C of a mixture of bulk oxides in three different stoichiometries in order to form new phases and modify their textural properties. Tests of stability against reduction were obtained by thermoprogrammed reduction, and kinetic studies of the sulfidation reaction were carried out in a the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 10 publications
0
46
0
1
Order By: Relevance
“…Sorbents of the ZFT(a) series were subsequently calcined at 1100ºC to facilitate the progress of spinel formation. 7 The samples obtained were named ZFT(b). Within each series, mixtures of three different stoichiometries were prepared in order to obtain different chemical compositions and textural properties ( Table 1).…”
Section: Experimental Methods and Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sorbents of the ZFT(a) series were subsequently calcined at 1100ºC to facilitate the progress of spinel formation. 7 The samples obtained were named ZFT(b). Within each series, mixtures of three different stoichiometries were prepared in order to obtain different chemical compositions and textural properties ( Table 1).…”
Section: Experimental Methods and Conditionsmentioning
confidence: 99%
“…The use of zinc-titanates improved reductive and thermal stability compared to zinc ferrites. [3][4][5][6][7] Although sulphur retention is considered a major topic in IGCC gas cleaning, other corrosive or toxic species present in gasification flue gases are also of great interest. This is the case of arsenic and selenium, which are classified by the Clean Air Amendments as elements of major environmental concern.…”
Section: Introductionmentioning
confidence: 99%
“…12 Outside of the United States, work on sorbent development has been very prolific, particularly in western European countries such as the Netherlands, 80,81 England, and Spain. 82 In order for a metal oxide to be considered suitable for high-temperature desulfurization, the material must exhibit desirable properties in the following areas: The feasibility of operating a moving-bed high-temperature desulfurization system in an economically competitive and technically feasible manner currently restricts its use to a temperature window between 400-750 °C (752-1472 °F) and pressures above 10 atmospheres 1-8 during absorption. Operation below 400 °C does not take full advantage of higher system efficiency compared to low-temperature cleanup systems, while operation above 750 °C requires a tradeoff between more sophisticated material properties/higher capital costs and reliability of process operation.…”
Section: -7mentioning
confidence: 99%
“…However, in strongly reducing atmospheres and at temperatures above 650 7C, ZnO is reduced to metallic zinc and volatilized (Ayala and Marsh 1991; Garcia et al 1997). To prevent sorbent reduction, ZnO is combined with other metal oxides.…”
Section: Zinc-based Sorbentsmentioning
confidence: 99%
“…Additionally, a combination of CuO with zinc ferrite has been studied by Garcia et al(1997) to develop superior sorbents even though the addition of Cu has not shown any stabilization effect on bulk zinc ferrite sorbents. However, it was found by Pineda et al (1997) that Cu addition to zinc ferrite improved the sorbent performance through its migration towards the sorbent surface and through its enhancement of the formation of spinel structures.…”
Section: Copper-based Sorbentsmentioning
confidence: 99%